ANALISIS MASALAH DAN TANTANGAN DALAM MENGELOLA HUBUNGAN DENGAN PELANGGAN DI PT. AGUNG SOLUSI TRANS: STRATEGI KOMUNIKASI UNTUK MENINGKATKAN LOYALITAS PELANGGAN - Nalibaratawati, Rakhmia; Pratiwi Putri, Kartika; Nur Hamidah, Filah (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
The main objective of this research is to identify and analyze the factors influencing service quality and communication at PT. Agung Solusi Trans, focusing on efforts to enhance relationships with customers, effectively resolve arising disputes, and strengthen customer loyalty. The research methodology employed at PT. Agung Solusi Trans utilizes a qualitative approach with a post-positivist stance. This study aims to comprehend the natural conditions within the company and analyze emerging issues. Data collection involves participatory observation and interviews with company employees, which are subsequently analyzed through data reduction, data presentation, and conclusion drawing. This approach allows researchers to gain a deep understanding of the company's services and existing issues from an internal perspective. The findings reveal that the primary challenges faced by PT. Agung Solusi Trans include difficulties in managing relationships with the general public and ineffective communication. Consequently, these challenges lead to decreased customer loyalty and suboptimal satisfaction levels. This indicates the need for the company to improve customer understanding of the services offered, provide comprehensive and accessible information, and enhance communication processes to better meet customer expectations. By addressing these issues, PT. Agung Solusi Trans aims to enhance its reputation, gain customer trust, and achieve sustainable business growth.